SEM PLS Evidence on Workload, Workforce Adequacy, Job Satisfaction, and Performance: Bukti SEM PLS tentang Beban Kerja, Kecukupan Tenaga Kerja, Kepuasan Kerja, dan Kinerja Karyawan - Octaviani, Elistia; Waluyo, Minto (Academia Open, 2026)
General Background: Employee performance is a critical factor in sustaining production continuity and competitiveness in small-scale manufacturing industries. Specific Background: In a paving manufacturing company applying a make-to-stock system, production targets are frequently achieved through overtime, indicating underlying performance challenges related to workload and workforce conditions. Knowledge Gap: Limited empirical evidence explains how workload, workforce adequacy, work environment, and motivation interact with job satisfaction and performance within small manufacturing contexts using SEM-PLS analysis. Aims: This study examines the relationships among workload, work environment, work motivation, and workforce adequacy on job satisfaction and employee performance, including the mediating role of job satisfaction. Results: The findings reveal that workload significantly affects job satisfaction, while workforce adequacy and job satisfaction significantly contribute to employee performance; conversely, work environment and work motivation show no significant relationships. Job satisfaction mediates the linkage between workload and employee performance. Novelty: This study provides SEM-PLS empirical evidence highlighting job satisfaction as a mediating construct in small-scale manufacturing settings, particularly within paving production systems. Implications: The results suggest that managing workload balance and ensuring sufficient workforce allocation are essential strategies for improving employee performance and supporting sustainable production outcomes in similar industrial contexts. Highlights: Excess task demands correlate with changes in employee satisfaction levels. Adequate staffing contributes directly to improved work outcomes. Satisfaction serves as an intermediary linking task demands to output quality. Keywords: Workload, Workforce Adequacy, Job Satisfaction, Employee Performance, SEM-PLS